Sosialisasi Kenakalan Remaja : Bahaya Narkoba dan Judi Online pada Karang Taruna Desa Babulang Kecamatan Kalianda Kabupaten Lampung Selatan Lampung - Nurmalia, Gustika; Ridwansyah, Ridwansyah; Juwita, Safna; Farhana, Nur Laila; Herfina, Inne Dwi; Arisca, Nurmalita; Sari, Defya; Ayasar, Prayogi Putra; Irfansyah, Nanda; Ramadhani, Mutiara (Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
Juvenile delinquency has become one of the worrying social problems, especially with the increase in cases of drug abuse and involvement in online gambling. This community service activity (PKM) aims to identify the effectiveness of socialization about the dangers of drugs and online gambling to members of the Youth Organization as a preventive effort in reducing juvenile delinquency. The method used is socialization through group discussions and the dissemination of educational materials. The results of this activity showed an increase in participants' knowledge and understanding of the risks and negative consequences of drugs and online gambling.